THE INTERNALIZATION OF ISLAMIC CHARACTER EDUCATION IN ENGLISH LANGUAGE TEACHING - Amalul - Umam; Mohammad - Sahril (STKIP PGRI Jombang, 2020)
Strengthening character education (PPK) is one of the main features in the Curriculum 2013. This is something new for some teachers, especially pre-service teachers. This study investigated the understanding of pre-service teachers about Al-Zarnuji’s Islamic characters and the internalization of the characters during their learning processes. Observation, documentation and open-ended questionnaire were employed in the study. The findings showed that pre-service teachers were familiar with the characters and could internalize them. The study suggests that the internalization of characters needs to be integrated in the learning processes from which pre-service teachers get used to the characters.